2018
DOI: 10.3892/ol.2018.8231
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided radiofrequency ablation enhances natural killer-mediated antitumor immunity against liver cancer

Abstract: For patients with liver cancer who are not sufficiently fit for surgical resection, radiofrequency ablation (RFA) is an effective and low risk treatment modality; however, the mechanism underlying this procedure is not fully understood. In the present study, a series of experiments were conducted, which demonstrated that RFA therapy stimulates innate antitumor immunity via directly enhancing natural killer (NK) cell cytotoxicity, thus achieving a favorable outcome for patients with liver tumors. It was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
9
0
1
Order By: Relevance
“…Radiofrequency ablation (RFA) is an effective and low risk treatment for hepatocellular carcinoma, and is especially suitable for patients with liver cancer, which are not suitable for operation. A total of five New Zealand white rabbits aged between two to three months, weighing 2.5-3.0 kg were randomly selected and established as an animal model of hepatocellular carcinoma in the novel studies of Mo et al [69]. Two weeks later, the expression level of NKG2D receptors on NK cells in the white rabbits were all detected by flow cytometry and the levels of IFN-γ and TNF-α were tested by ELISA on basis of hematoxylin and eosin (H&E) staining of the liver tissue on the slices.…”
Section: Tnf-alpha Secreted By Nk Cells Exerts Anti-hepatocarcinoma Amentioning
confidence: 99%
“…Radiofrequency ablation (RFA) is an effective and low risk treatment for hepatocellular carcinoma, and is especially suitable for patients with liver cancer, which are not suitable for operation. A total of five New Zealand white rabbits aged between two to three months, weighing 2.5-3.0 kg were randomly selected and established as an animal model of hepatocellular carcinoma in the novel studies of Mo et al [69]. Two weeks later, the expression level of NKG2D receptors on NK cells in the white rabbits were all detected by flow cytometry and the levels of IFN-γ and TNF-α were tested by ELISA on basis of hematoxylin and eosin (H&E) staining of the liver tissue on the slices.…”
Section: Tnf-alpha Secreted By Nk Cells Exerts Anti-hepatocarcinoma Amentioning
confidence: 99%
“…At present, recurrence and metastasis are key factors that limit clinical outcomes of HCC patients [3]. Immune escape is also an important prerequisite for tumor recurrence and metastasis [19]. NK cells are important cells in the innate immune system, and they can quickly identify and kill tumor cells [18, 20].…”
Section: Discussionmentioning
confidence: 99%
“…RFA causes protein denaturation and coagulative necrosis by heating, and blocks the blood supply to the tumor, further causing tumor cell ischemia and delaying tumor growth [32,33]. At the same time, RFA can also enhance the immunity of patients by promoting the immune function of T cells, natural killer cells and macrophages, thereby limiting tumor cell proliferation [34]. However, clinical data indicated that RFA cannot significantly prolong the patients' five-year survival rate [6].…”
Section: Discussionmentioning
confidence: 99%